FAKTOR – FAKTOR YANG MEMPENGARUHI PROFITABILITAS (Studi Pada Bank Perkreditan Rakyat (BPR) Di Provinsi Jambi) - Tri Joko Febriyono (Magister Ilmu Akuntansi Universitas Jambi, 2015)
This research was conducted to examine the effect of direct and indirect Assets Quality (KAP), Non Performing Loan (NPL), Loan to Deposit Ratio (LDR), Capital Adequacy Ratio (CAR), Operating Expenses Operating Income (BOPO), for Return on Assets (ROA) in the rural banks (BPR) in Jambi Province. The populatin in this reaserch are 19 Banks. According these population as a sample are 14 BPR in Jambi Province the perio of 2012 until 2014. From the research simultaneously affect the significance of the five variables Return on Assets (ROA). While partially shows that the Assets Quality (KAP), Non Performing Loan (NPL), Loan to Deposit Ratio (LDR) not direct influence over Return on Assets (ROA). Indirectly Non Performing Loan (NPL) no effect bassed on Return on Assets (ROA) through Capital Adequacy Ratio (CAR), but Non Performing Loan (NPL) effect bassed on Return on Assets (ROA) through Operating Expenses Operating Income (BOPO). Key words: Productive Assets Quality KAP), Non Performing Loan (NPL), Loan to Deposit Ratio (LDR),Capital Adequacy Ratio (CAR), Operating Expenses Operating Income (BOPO), dan Return on Assets (ROA).